Polyclonal Intravenous Immunoglobulin for the Prophylaxis and Treatment of Infection in Critically Ill Adults - Kevin B Laupland (Canadian Journal of Infectious Diseases)
Infection is a major cause of morbidity and mortality in critically ill patients. Despite advances in technology, its mortality rate has changed minimally over the past two decades, and new therapies are needed. Polyclonal intravenous immunoglobulin (IVIG) has been investigated both as a preventive and a treatment modality for sepsis and septic shock in critically ill adult patients. Prophylaxis with IVIG has been shown to reduce significantly the incidence of infection, particularly pneumonia, in selected postsurgical intensive care patients. However, it does not reduce mortality. The risk-benefit and cost effectiveness of this therapeutic intervention have not been determined, and its routine use is therefore not recommended. Treatment with IVIG has been shown in a number of small trials and a meta-analysis to reduce dramatically sepsis and septic shock mortality. However, a large, unpublished randomized trial has apparently shown no mortality benefit with this therapy. Despite limited evidence, IVIG has become the standard of care for the management of group A streptococcal toxic shock syndrome. At present, clinical equipoise exists for the use of IVIG in the treatment of sepsis and septic shock, and further study is needed.